2018
DOI: 10.3390/sports6040121
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Responses to an Undulating Resistance Training Program in Free-Living Conditions: A Case Study in a Collegiate Athlete

Abstract: The purpose of this case study was to evaluate the response in heart rate variability via the parasympathetically-mediated metric of the log-transformed root mean square of successive R-R interval differences (lnRMSSD) to weekly variations in total volume-load (TVL) during an 18-week periodized strength training program in a competitive collegiate hockey athlete. The program consisted of three 60–90 min full-body exercise sessions per week with at least 24-h of rest between each session. Daily lnRMSSD measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Kliszczewicz et al (2014) showed that heart rate response in Cindy WOD reached values between 76.0% to 96.0% of peak heart rate and this response would be caused primarily by parasympathetic withdrawal and an increase in sympathetic activity. The variation in the RMSSD index has a higher correlation with volume than the intensity (Holmes et al, 2018). Thus, the smaller this variation, the greater the parasympathetic activity and the ability to withstand the exercise stress, a factor that is linked to the level of physical conditioning (Hernández-Cruz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Kliszczewicz et al (2014) showed that heart rate response in Cindy WOD reached values between 76.0% to 96.0% of peak heart rate and this response would be caused primarily by parasympathetic withdrawal and an increase in sympathetic activity. The variation in the RMSSD index has a higher correlation with volume than the intensity (Holmes et al, 2018). Thus, the smaller this variation, the greater the parasympathetic activity and the ability to withstand the exercise stress, a factor that is linked to the level of physical conditioning (Hernández-Cruz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%